Activities and Postantibiotic Effects of Gemifloxacin Compared to Those of 11 Other Agents against Haemophilus influenzae and Moraxella catarrhalis - Davies, Todd A. (American Society for Microbiology, 2000)
The activity of gemifloxacin against Haemophilus influenzae and Moraxella catarrhalis was compared to those of 11 other agents. All quinolones were very active (MICs, ≤0.125 μg/ml) against 248 quinolone-susceptible H. influenzae isolates (40.7% of which were β-lactamase positive); cefixime (MICs, ≤0.125 μg/ml) and amoxicillin-clavulanate (MICs ≤4.0 μg/ml) were active, followed by cefuroxime (MICs, ≤16.0 μg/ml); azithromycin MICs were ≤4.0 μg/ml. For nine H. influenzae isolates with reduced quinolone susceptibilities, the MICs at which 50% of isolates are inhibited (MIC(50)s) were 0.25 μg/ml for gemifloxacin and 1.0 μg/ml for the other quinolones tested. All strains had mutations in GyrA (Ser84, Asp88); most also had mutations in ParC (Asp83, Ser84, Glu88) and ParE (Asp420, Ser458), and only one had a mutation in GyrB (Gln468). All quinolones tested were equally active (MICs, ≤0.06 μg/ml) against 50 M. catarrhalis strains; amoxicillin-clavulanate, cefixime, cefuroxime, and azithromycin were very active. Against 10 H. influenzae strains gemifloxacin, levofloxacin, sparfloxacin, and trovafloxacin at 2× the MIC and ciprofloxacin at 4× the MIC were uniformly bactericidal after 24 h, and against 9 of 10 strains grepafloxacin at 2× the MIC was bactericidal after 24 h. After 24 h bactericidal activity was seen with amoxicillin-clavulanate at 2× the MIC for all strains, cefixime at 2× the MIC for 9 of 10 strains, cefuroxime at 4× the MIC for all strains, and azithromycin at 2× the MIC for all strains. All quinolones except grepafloxacin (which was bactericidal against four of five strains) and all ß-lactams at 2× to 4× the MIC were bactericidal against five M. catarrhalis strains after 24 h; azithromycin at the MIC was bactericidal against all strains after 24 h. The postantibiotic effects (PAEs) against four quinolone-susceptible H. influenzae strains were as follows: gemifloxacin, 0.3 to 2.3 h; ciprofloxacin, 1.3 to 4.2 h; levofloxacin, 2.8 to 6.2 h; sparfloxacin, 0.6 to 3.0 h; grepafloxacin, 0 to 2.1 h; trovafloxacin, 0.8 to 2.8 h. At 10× the MIC, no quinolone PAEs were found against the strain for which quinolone MICs were increased. Azithromycin PAEs were 3.7 to 7.3 h.